The Indore population’s morphometric study of the nutrient foramina of the dried radius - Singh, Pawika; Modi, Vimal; Singh, Anand K.; Singh, Nirmal R. (International Journal of Research in Medical Sciences, 2023)
Background: Bone formation, growth and its vitality necessitates blood supply. Nutrient artery is the key source of blood supply to the long bone apart from the other important sources like periosteal, metaphyseal and epiphyseal arteries. Nutrient foramina allow nutrient artery. Typically, the direction of the nutrient foramina is towards the elbow joint in radius, away from its growing end. Knowledge of foramen index, number, direction and size of the nutrient foramina assists the surgeon to take and exact section of bone in case of bone resection and transplantation techniques. The aim of the present study is to determine the number, position, size direction of the nutrient foramina and the Foramen Index of the human dry radius bones. Methods: In the present study, 100 radius bones of unknown age and sex were taken into consideration from the department of anatomy Index Medical College, Indore (MP), India. Results: Most of the foramen was observed on the anterior surface of the bone. Nutrient foramina was found to be absent in 4 right sided and 3 left sided bones. The foramen index on right side was 34.92±4.97 cm whereas on the left side 34.79±4.43 cm. The nutrient foramen was directed towards the proximal end of radius in all the bones studied. Conclusions: In the present study the average length of the bone and foramina of the size larger are more on the right side when compared to the left side. The foramina are located mostly in the middle third of the bone of the anterior surface. This study may add to the present statistical data available on foramen index number of foramen and their location in the population of Indore region, during recent orthopaedic techniques like bone resection and transplantation.